The Application of Scientific Coaching in Improving Learning Quality at Junior High Schools Negeri 4 Geyer, Grobogan Regency - Tri Yuli Astuti; Endang Wuryandini; Rosalina Br Ginting (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe and analyze the implementation of academic supervision based on scientific coaching at SMP Negeri 4 Geyer through a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, then analyzed through presentation, reduction, and conclusion. The study results indicate that 1. planning of academic supervision based on scientific coaching implemented through initial meetings between the principal and teachers to analyze teacher development needs in improving the quality of learning by analyzing educational report cards. Furthermore, the principal forms a work team tasked with compiling an annual work plan based on the academic report card analysis results. Afterward, the work team compiles objectives, plans, strategies, and coaching schedules. The work team also compiles assessment instruments to understand the curriculum, teaching modules, and observation sheets. 2. The implementation of coaching-based academic supervision is carried out in three stages: observation, pre-observation, and post-observation. Pre-observation is carried out by checking the learning administration and observation by observing the learning process in the classroom. After observation, post-observation is carried out. In this post-observation, the principal conducts coaching on the learning process that the teacher has carried out. 3. Evaluation and follow-up of coaching-based academic supervision. In this stage, the principal evaluates and follows up by compiling plans and programs for future coaching-based academic supervision. Based on research results, supervision Coaching-based academics can improve the quality of learning and help teachers enhance learning practices